Clinical atlas of burn management - Sarabahi, Sujata (Jaypee Brothers Medical, 2011)
Clinical Atlas of Burn Management is a sequel to Principles and Practice of Burn Care. Beginning with an introduction to the causes and classification of burns, this atlas guides students and surgeons through the determination of the damage caused by the burn and how to manage the wound. Assisted by well-illustrated colour photographs, the book presents different types of injury, including electric burns, chemical burns and radiation